2017
DOI: 10.1111/jhn.12509
|View full text |Cite
|
Sign up to set email alerts
|

Future Dietitian 2025: informing the development of a workforce strategy for dietetics

Abstract: Background: Healthcare is changing and the professions that deliver it need to adapt and change too. The aim of this research was to inform the development of a workforce strategy for Dietetics for 2020-2030. This included an understanding of the drivers for change, the views of stakeholders and recommendations to prepare the profession for the future. Methods: The research included three phases: (i) establishing the context which included a literature and document review (environmental scan); (ii) discovering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 9 publications
2
95
0
Order By: Relevance
“…The importance of preparing the profession for the future of eHealth was also highlighted by Hickson et al (2017) who identified 'embracing advances in science and technology as one of the five themes to inform the development of a workforce strategy for 2020-2030 for dietetics' (37) . Their recommendation specifically related to technology to prepare the profession for the future, was: 'Consider how to support dietitians to keep pace with technological advances and how to facilitate the uptake of new technology, including expanding the evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of preparing the profession for the future of eHealth was also highlighted by Hickson et al (2017) who identified 'embracing advances in science and technology as one of the five themes to inform the development of a workforce strategy for 2020-2030 for dietetics' (37) . Their recommendation specifically related to technology to prepare the profession for the future, was: 'Consider how to support dietitians to keep pace with technological advances and how to facilitate the uptake of new technology, including expanding the evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research commissioned by national dietetics bodies in the USA, the UK and Canada has attempted to inform dietetics workforce development and hypothesise on the future direction of the profession. However, to the authors’ knowledge, no national approaches to date have broadly explored dietetics workforce preparation and the impact of associated challenges from the perspective of dietetics educators.…”
Section: Introductionmentioning
confidence: 99%
“…While this analysis indicates that the research presented at the DAA conference is largely practice driven, the research is undoubtedly important in developing the evidence base that underpins nutrition and dietetic practice . Limited availability of competitive grant round funding poses challenges to undertake large and complex high‐quality studies that continue to extend the evidence base .…”
Section: Discussionmentioning
confidence: 99%